Pharmacological prophylaxis of delirium in cardiosurgery - Yu. L. Shevchenko; Yu. I. Gorokhovatskii; M. N. Zamiatin; A. R. Sedrakian; A. V. Vakhliaev; G. G. Borshchev (Вестник хирургии имени И.И. Грекова)
The objective of the study is to evaluate the effect of perioperative administration of dexmedetomidine on the frequency of delirium after myocardial revascularization.Material and methods. A retrospective analysis of the results of 1733 operations of myocardial revascularization was performed, as well as a prospective comparative study of postoperative period features in 568 patients.Results. The use of perioperative administration of dexmedetomidine at a rate of 0.2–0.4 μg/(kg•min) resulted in a significant (3.4 times,) decrease in the frequency of delirium, and in the case of the development of a syndrome resulted in the reducing its duration from (3,24±1,6) to (1,6±0,7) days and the need for prolonged artificial lungs ventilation (ALV), a decrease in the dose of haloperidol for arresting excitation.Conclusion. Perioperative infusion of dexmedetomidine reduces the frequency of delirium after coronary artery bypass grafting (CABG). In the case of delirium progression, the inclusion of dexmedetomidine in therapy reduces the duration of delirium, the need for ALV, and reduces the need for neuroleptics.